Toward the Efficient Impact Frontier - McCreless,Michael (2017)
For many years, the field of impact investing played host to great debates that involved seemingly irreconcilable positions: Was it possible to achieve both market-rate financial returns and meaningful social impact? Could philanthropic funding coexist effectively with commercial investment? Now, as the field reaches a new stage of maturity, leading social finance organizations are developing models that bring greater sophistication to the work of evaluating investment options. These models, like the investors that create them, vary widely. But they reflect a shared commitment to moving beyond simple either-or choices—and to moving from broad questions to specific solutions.